Genetic Variation in Osteopontin Gene Is Associated with Susceptibility to Sarcoidosis in Slovenian Population. Issue 6 (2nd June 2013) - Maver, A.; Medica, I.; Salobir, B.; Tercelj, M.; Peterlin, B.
Abstract : Sarcoidosis is a systemic inflammatory disease characterised by appearance of granulomas. Precise etiology has not been elucidated. Osteopontin (Opn) is a Th1 cytokine whose levels have been found increased in granulomas and serum samples from patients with sarcoidosis. We investigated whether genetic variation in Osteopontin gene (OPN) gene contributes to susceptibility to sarcoidosis. Haplotype-block structure in the OPN gene region was investigated using data from HapMap project. Three representative SNPs have been selected from each block of SNPs in linkage disequilibrium (rs11730582-C/T, rs11728697-C/T and rs4754-C/T). Genotyping was performed using TaqMan SNP Genotyping Assays on a sample of 165 patients and 284 controls. Statistical analyses of association were performed using Chi-Square test and algorithms implemented in the haplo.stats and PHASE packages. Genotyping analysis revealed a significant difference in genotype frequencies at rs4754 polymorphism in groups of patients and controls under recessive genetic model ( p =0.036, OR=1.99, 95%CI=1.04-3.82), CC homozygotes being significantly over-represented in the patients group. However these results failed to reach significance after correction for multiple testing ( p =0.25). The frequencies of predicted haplotypes differed between patient and control groups, frequency of TTT haplotype was found to be significantly decreased in the group of patients with sarcoidosis ( p =0.014, OR=0.40, 95%CI=0.20-0.79). Our results suggest that variation in the OPN gene might be significantly associated with sarcoidosis and that the TTT haplotype in OPN may act as a protective factor in sarcoidosis.